Eksplorasi Penggunaan Peta Digital dalam Konsep Pemahaman Geografi Lokal Siswa Sekolah Dasar (SD) - Inayah Maulaya; Muhammad Fariz Irfiyan; Mila Khoiru Zulfa; Muhammad Nofan Zulfahmi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research aims to explore the use of digital maps in enhancing the local geography understanding of elementary school students. (SD). Digital maps, which offer geographic information interactively and visually, have great potential in helping students understand geographic concepts related to their surroundings. The use of digital maps in local geography education in elementary schools is an increasingly popular educational innovation in Indonesia. Digital maps help students understand geography concepts and support educational principles. Local geography learning, which includes knowledge about location, distance, and the relationship between humans and nature in the surrounding area, can be better understood through the use of digital maps. This research uses the Library Research method. The results of the study show that digital maps help students more easily recognize and identify various elements of local geography, such as geographical location, topographical differences, and the distribution of natural and human resources. Additionally, the use of digital maps also increases students' motivation and engagement in learning, as the teaching materials are presented in a more interesting and interactive manner. Thus, this research concludes that the integration of digital maps in local geography learning can enrich students' learning experiences, clarify their understanding of geographical concepts, and improve the quality of geography education at the elementary school level.